Mild cognitive impairment and dementia : definitions, diagnosis, and treatment - Smith, Glenn E. (Oxford University Press, 2013)
In 2011, National Institute on Aging and Alzheimer's Association joint task forces released proposed criteria for Alzheimer' disease diagnosis. These proposals included revisions to the nearly 30-year-old NINDS-ADRDA criteria for Alzheimer's diagnosis and added criteria for diagnosis of Mild Cognitive Impairment (MCI) due to Alzheimer's disease. The same year the American Psychiatric Association proposed new criteria for major and minor neurocognitive disorders (the entities previously known as dementia and mild cognitive impairment, respectively). These new criteria reflect the research and c.